THE CASE STUDY ON THE IMPACT OF CRUDE OIL PRICE AFFECTING THE INFLATION RATE IN MALAYSIA - Yeoh Wee Win (Jurnal Syntax Transformation, 2023)
The uncertainty in the economic growth had been highly contributed by multiple factors which does not exclude the suggestion on the impact from the crude oil prices. The major impact from the crude oil prices had been strong in influencing the rising prices of the consumer’s goods and services which often translate into the rising inflation for the country. With reference to this., the objective for the current study will focus into exploring the investigation on the impact of the crude oil price against the impact on the inflation rate within the economic condition of Malaysia. The quantitative study method had been developed where the results and findings for the study had achieved the outcome identifying the significant positive relationship between the crude oil price in affecting the inflation rate in Malaysia. The outcome for the research had been crucial address towards the achievement in the academic study reducing the gap in literature review as well as developing further reference for the individuals and businesses to plan the financial resources in the future in Malaysia.